Complete data analysis using R your applied manual - Lehmann, Marco (Los Angeles SAGE, 2023)
This step-by-step guide shows you how to use R to get data analysis right. The book explores the entire process of analysis, covering key steps from preparing your data to putting your analysis together and writing up your findings. It helps you get to grips with doing different statistical techniques in R and: 1. Equips you with practical data visualisation tools to create graphs and tables. 2. Shows you how to prepare and present your research for assessment, publication and dissemination. 3. Covers key issues facing today's social scientists, such as making research reproducible. Features include an introduction to each chapter, and end-of-chapter exercises to check your understanding of the material. The online resources for this text include data sets that you can perform your own analysis on, and links to publications that are relevant to programming with R. A good starting point for any postgraduate student conducting a research project, this book will help you develop your statistics and programming knowledge and get quickly up to speed."--
Quick start - basic training in r functions -- Getting your data in and out of R -- Preparing the data for analysis -- Descriptive and exploratory data analysis -- Graphical data analysis -- Inferential statistics I: a completely randomised factorial design -- Inferential statistics II: a multiple regression analysis -- Preparing tables for publication -- Preparing graphics for publication -- Data simulation -- Putting it all together: the structure of a statistical analysis.
Includes bibliographical references and index.
Keywords: R (Computer program language); Research -- Statistical methods -- Data processing; Social sciences -- Research -- Statistical methods